2017
DOI: 10.3892/etm.2017.4862
|View full text |Cite
|
Sign up to set email alerts
|

Elevated levels of soluble fractalkine and increased expression of CX3CR1 in neuropsychiatric systemic lupus erythematosus

Abstract: Abstract. The aim of the present study was to determine the levels of soluble fractalkine (sFKN) and expression of CX3CR1 in neuropsychiatric systemic lupus erythematosus (NPSLE). Disease activity of SLE was assessed using the SLE Disease Activity Index (SLEDAI). The mRNA expression levels of CX3CR1 and FKN were quantified using reverse transcription-quantitative polymerase chain reaction. Levels of sFKN in the serum and cerebrospinal fluid (CSF) were measured using enzyme-linked immunosorbent assays. The mRNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 35 publications
(40 reference statements)
0
8
0
Order By: Relevance
“…Changes in CX3CL1 concentration have been found in other diseases that course with inflammation. For example, soluble CX3CL1 levels are increased in plasma and CSF of patients with lupus erythematosus ( Guo et al, 2017 ). In addition, plasma CX3CL1 levels are augmented in individuals with type-2 diabetes ( Sindhu et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Changes in CX3CL1 concentration have been found in other diseases that course with inflammation. For example, soluble CX3CL1 levels are increased in plasma and CSF of patients with lupus erythematosus ( Guo et al, 2017 ). In addition, plasma CX3CL1 levels are augmented in individuals with type-2 diabetes ( Sindhu et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…FKN levels are significantly higher in cerebrospinal fluid samples from patients with SLE-associated involvement of the central nervous system (termed neuropsychiatric SLE) than from healthy subjects, and the FKN levels correlate with treatment effects. 76 Similarly, both cerebrospinal fluid and serum levels of FKN are significantly higher in patients with diffuse neuropsychiatric SLE than in patients with other SLE subtypes or in healthy subjects. 76 These results further support a role for FKN in the pathogenesis of SLE, at least neuropsychiatric SLE, and suggest that FKN could serve as a therapeutic target and/or a biomarker for SLE disease activity.…”
Section: Fkn–cx3cr1 Axis Involvement In the Pathogenesis Of Rheumaticmentioning
confidence: 97%
“… 76 Similarly, both cerebrospinal fluid and serum levels of FKN are significantly higher in patients with diffuse neuropsychiatric SLE than in patients with other SLE subtypes or in healthy subjects. 76 These results further support a role for FKN in the pathogenesis of SLE, at least neuropsychiatric SLE, and suggest that FKN could serve as a therapeutic target and/or a biomarker for SLE disease activity.…”
Section: Fkn–cx3cr1 Axis Involvement In the Pathogenesis Of Rheumaticmentioning
confidence: 97%
“…FKN represents one of the factors associated with tissue damage and the accumulation of immune cells into the damaged area (30). Accumulated evidence has suggested that FKN plays a significant role in the disease progression of LN (31). Moreover, we have previously demonstrated that FKN expression was increased in LN model mice and HK-2 cells that were stimulated with lipopolysaccharide, whereas the protein expression of FKN was decreased after methylprednisolone therapy (32).…”
Section: Introductionmentioning
confidence: 99%